“Virtuosas e inocentes como o lyrio”: produção de subjetividades femininas em jornais cearenses para mulheres (1875-1907) - Medeiros, Nathássia Matias de (2020)
This research aimed to analyze the speeches about female life present in Ceará newspapers for women published between 1875 and 1907, in order to think about the female subjectivities that these newspapers intended to give rise to. From the last decades of the 19th century, Fortaleza, following the movement of the main Brazilian cities, underwent intense modernization, urbanization and reformulation of social relations. The new sociability developed at Ceará’s capital required the construction of new life references for women, in line with the social changes that were taking place. The press was seen as a great way of disseminating progress and education in Ceará, considered by the “elites” as backward and ignorant. Methodologically, this research works based on theoretical and methodological tools proposed by Michel Foucault. After consulting public collections in three Brazilian states, a set of seven titles from Ceará newspapers for women that make up the corpus of this research was compiled: A Brisa, Lírio, O Orvalho, O Bond, O Bemteví, Pimpão and O Astro, totaling forty two numbers of newspapers, published between 1875 and 1907. From a genealogic point of view, we considered the disciplinary, pedagogical and biopolitical strategies through which newspapers operated to govern women readers, educating their bodies and subjectivities, were observed. Parameters of virtue, sexuality, beauty and family dynamics were established through newspapers for women of the time. New values ​​were disseminated for female life in accordance with the new social feature that was configured in the late 19th and early 20th centuries. The speeches of this press sought to reach the bodies, sexualities, behaviors, subjectivities of their readers. Newspapers functioned not only as a source of information, but also as means of governing both the individual body and the body of the population. A government on life, which sought to build gender standards in order to meet political and social interests. We conclude that the speeches of the newspapers from Ceará for women analyzed sought to act in the production of new female subjectivities, which would serve the political purposes of a power over life on the rise. The aim was to produce docile, useful and regulated bodies, necessary for the maintenance of factory work, hygiene and the bourgeois family, supporting the capitalist society in consolidation.